Gallbladder Metastasis from Renal Cell Carcinoma - Kawahara, Takashi (S. Karger AG, 2010)
A 73-year-old female was operated with radical nephrectomy and cholecystectomy for renal cell carcinoma and suspected gallstones after 9 courses of sunitinib treatment. Gallbladder specimen showed gallbladder metastasis originating from the renal cell carcinoma. Gallbladder metastasis from renal cell carcinoma is rare. Here, we discuss a case of gallbladder metastasis from renal cell carcinoma.